Do house price developments spill over across euro area countries? Evidence from a Global VAR - Paul Hiebert; Isabel Vansteenkiste (European Central Bank (ECB), 2009)
This paper empirically assesses the prospects for house price spillovers in the euro area, where co-movement in house prices across countries may be particularly relevant given a general trend with monetary union toward increasing linkages in trade, financial markets, and general economic conditions. The application involves a Global VAR for three housing demand variables (real house prices, real per capita disposable income, and the real interest rate) on the basis of quarterly data for 10 euro area countries (Belgium, Germany, Ireland, Spain, France, Italy, the Netherlands, Austria, Portugal and Finland) over the period 1989-2007. The results suggest limited house price spillovers in the euro area, with evidence of some overshooting in the first 1-3 years after the shock, followed by a long run aggregate euro area impact of country-specific changes in real house prices related in part to the country's economic weight. This contrasts with the impacts of a shock to domestic long- term interest rates, with the latter causing a permanent shift in house prices after around 3 years. Underlying this aggregate development are rather heterogeneous house price spillovers at the country level, with a strong importance for economic weight in the euro area in governing their general magnitude, while geographic proximity appears to also play a role.
Keywords: R21; R31; C32; 330; Global VAR (GVAR); house price; international linkages; Immobilienpreis; Spillover-Effekt; VAR-Modell; Eurozone